MASALAH HUKUM DALAM PENGHIBAHAN MILIK ATAS TANAH BERDASARKAN UNDANG-UNDANG POKOK AGRARIA - Khairunnisah Khairunnisah (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
ABSTRACTThat in Indonesia the earth, water and natural resources contained therein dominated by esarnya state for the benefit of the people. With the rights of control of the state, the state is authorized to provide land rights. One of the parcels of land are considered the most perfect is the title for the land that is the strongest and fullest. Of property rights over land, rights holders entitled to take advantage of their rights to the land to its interests, including transferring it to others. There are several intermediate forms of land rights, such as the sale and purchase, exchange, lease, etc., all of which on average are reciprocal. However there is one form of which we are familiar with Grant. Grant is a persetujun the penghibah, at a time when its life, freely and with irrevocable, handed some object for the purposes of the grant recipient receives the submission and has ditur in article 1666 BW, whereas the definition of property rights is the right hereditary, the strongest and most are able to possess the land, with the provisions of article 6 of the BAL. Property rights can be switched and transferred to another party in accordance with article 20 of the BAL.